Investigating the reasons for the differences in the accessibility of renal replacement therapy in the public and private healthcare sectors in South Africa - Asmal, Zubair Mahomed (University of the Witwatersrand, Johannesburg, 2022)
The number of patients with kidney failure is increasing. This increase is secondary to an increase in the risk factors resulting in kidney disease, and will result in an increase in the number of patients requiring renal replacement therapy (RRT). South Africa has a two-tiered healthcare system, a public and a private sector. At present, there is a significant disparity in the number of patients receiving RRT in the two sectors with more in the private sector. This disparity has been attributed anecdotally to a lack of resources in the public sector and specific legislation, although no research have been done to confirm this. Health disparity in general is complex and involves an interplay between multiple factors, including historical, political, economic, legislative and environmental factors. The hypothesis is that the disparity in RRT is complex, based on multiple factors, and cannot be ascribed to only two factors. To test the hypothesis, we interviewed the stakeholders in the RRT industry regarding their perspectives of the causative factors. In total, 33 interviews were conducted, recorded, transcribed and analysed using the grounded theory from a constructivist angle. The objective of the analysis was to determine which factors contributed to t he number of patients receiving RRT in the public sector, compared with the private sector. As the renal transplantation programme is managed collectively by the two sectors, it was considered separately. Based on the interviews, five themes were extracted to explain the disparity. These themes follow the journey of a kidney failure patient from the factors that contributed to the condition, to being diagnosed and ultimately treated. The themes are the prevalence of kidney disease in the two populations, the decision-making process of who receives RRT, the accessibility of receiving RRT, the resources available for RRT and the impact of the transplantation. Each theme has subthemes and combined they form a holistic explanation to account for the disparity. This study identified possible causative mechanisms to explain the disparity. It is hoped that by uncovering these mechanisms, corrective Page 5 of 15 measures can be implemented, a more equitable and just healthcare service can be offered to all citizens and in the process save a multitude of lives
A research report submitted in partial fulfilment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, 2023
Keywords: Public health care; Private healthcare; Renal care South Africa; Public sector; Accessibility of healthcare; UCTD; SDG-3: Good health and well-being